Flow Synthesis of Iodonium Trifluoroacetates through Direct Oxidation of Iodoarenes by Oxone®; European Journal of Organic Chemistry; Vol. 2019, iss. 10 - Soldatova N. S. Nataliya Sergeevna; Postnikov P. S. Pavel Sergeevich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Virt T. (2019, 2019)
Title screen